Different Outcome in COVID-19 Patients with or without PPI Use: A Systematic Review and Meta-analysis - I Made Wisnu Wardhana; Saraswati Laksmi Dewi (Publication Department, Universitas Warmadewa, 2024)
Background The coronavirus disease (COVID-19) pandemic still happening and when it’s going to be resolved is not known. In this COVID-19 era, physicians need to better understand the risk and purpose of giving drugs that patients do not need. Proton pump inhibitors (PPI) are sometimes easily prescribed and misused by physicians. The study objective is to find out whether PPI use is associated with better or worse outcomes in patients with COVID-19. Method We searched retrospective studies in various publication libraries like PubMed, Embase, and CENTRAL from 2020 to 2022. Inclusion criteria were studied which differentiated patients with COVID-19 who regularly used PPI and control which is COVID-19 patients who did not use PPI. That study also needs to report the outcomes. The outcome was then divided into two categories which are good outcomes and worse outcomes consisting of severe COVID-19 needing oxygen therapy, admission to intensive care unit (ICU), acute respiratory distress syndrome (ARDS), shock or mortality, to get each study and total odd ratio (OR), 95% confidence interval, and weight. Studies that did not report the outcomes were excluded. We also analyze the data using a fixed or random effect model accordingly and asses the possibility of publication bias using Egger’s test. Case Seven of 11 studies with more than 30.000 COVID-19 patients were analyzed in this study. These patients were divided into 2 groups: patients with COVID-19 who were using PPI up to 30 days before being infected and COVID-19 patients who didn’t use PPI before. The total number of patients in the first group is 3531 patients and the second group is 38138 patients. After statistical analysis, we found that the data is heterogenous with p <0,05, I2 94,22% (95%CI 90,44-96,51%) suggesting the OR needs to be determined in the random effect model. We found that pooled OR is 1.99 (p 0.01, 95% CI, 1.18-3.38). Egger’s test for the possibility of publication bias is 0,64 (95%CI -7,24-4,93). Conclusion COVID-19 patients who use PPI are twice as likely to have a worse outcome than COVID-19 patients who don’t use PPI. This study is statistically significant with a low possibility of publication bias.